2020
DOI: 10.1038/s41598-020-77439-7
|View full text |Cite
|
Sign up to set email alerts
|

EEG-based trial-by-trial texture classification during active touch

Abstract: Trial-by-trial texture classification analysis and identifying salient texture related EEG features during active touch that are minimally influenced by movement type and frequency conditions are the main contributions of this work. A total of twelve healthy subjects were recruited. Each subject was instructed to use the fingertip of their dominant hand’s index finger to rub or tap three textured surfaces (smooth flat, medium rough, and rough) with three levels of movement frequency (approximately 2, 1 and 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…Power changes in theta, alpha, and beta frequency bands for the C3 electrode during discrimination and response periods, as well as the changes in ratios of frequencies, are in line with previous studies of tactile function. Tactile discrimination is often associated with changes in EEG activity recorded from the electrode C3/4, namely with the appearance of event related potentials or power changes in alpha and beta frequency bands [17][18][19][20][21][22][23][24][28][29]. For example, a relevant contribution of mu (8-15 Hz) and beta (16-30 Hz) frequency bands has been demonstrated for texture discrimination using a support vector machine classi er in electrodes recording from primary and secondary somatosensory cortex [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Power changes in theta, alpha, and beta frequency bands for the C3 electrode during discrimination and response periods, as well as the changes in ratios of frequencies, are in line with previous studies of tactile function. Tactile discrimination is often associated with changes in EEG activity recorded from the electrode C3/4, namely with the appearance of event related potentials or power changes in alpha and beta frequency bands [17][18][19][20][21][22][23][24][28][29]. For example, a relevant contribution of mu (8-15 Hz) and beta (16-30 Hz) frequency bands has been demonstrated for texture discrimination using a support vector machine classi er in electrodes recording from primary and secondary somatosensory cortex [23].…”
Section: Discussionmentioning
confidence: 99%
“…Tactile discrimination is often associated with changes in EEG activity recorded from the electrode C3/4, namely with the appearance of event related potentials or power changes in alpha and beta frequency bands [17][18][19][20][21][22][23][24][28][29]. For example, a relevant contribution of mu (8-15 Hz) and beta (16-30 Hz) frequency bands has been demonstrated for texture discrimination using a support vector machine classi er in electrodes recording from primary and secondary somatosensory cortex [23]. In addition, other complex functions such as orienting attention to an upcoming tactile event have also been associated with alpha and beta band modulation in sensorimotor regions [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroencephalography (EEG) studies showed that EEG contains patterns that change when the amount or roughness of tactile feedback changes [32,[43][44][45][46][47][48][49][50][51][52][53]. Genna et al showed an increase in the power of the theta band (4-7 Hz) for 500 ms after the stimulus onset, which was distributed across the cortex, with a focus around the contralateral somatosensory region.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, limited number of studies have employed deep learning in neurohaptics. An attempt was made to classify the surface texture during active exploration task ( Eldeeb et al, 2020 ) on a single EEG trial basis using Support Vector Machine (SVM) with features that are manually extracted from the raw EEG data. Another study developed a CNN model to identify the type of haptic interaction (passive vs. active) during visuo-haptic task on a single EEG trial basis as well ( Alsuradi and Eid, 2021 ).…”
Section: Introductionmentioning
confidence: 99%